1979
DOI: 10.1071/ar9790029
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem processes in semiarid grasslands. II.* Litter production decomposition and nutrient dynamics

Abstract: Changes in tissue nutrient concentration and nutrient uptake of a C3 native grassland and a sown C4 buffel grassland community, growing on infertile sandy red earth soils near Charleville, were studied. The seasonal pattern of litter production of grasslands in the grazed and ungrazed situation was also investigated. Studies in litter decomposition of Mitchell grass are reported. The decline in the above-ground biomass growth rate of both communities over the summer growing period corresponded with a similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…1). This is also true for perennial grasses elsewhere in Australia (Norman, 1963;Christie, 1979;Friedel, 1981) but contrary to Turner's (1998a, b) finding that N : P ratios in annual grasslands changed from assumed P-limitation (14-17) to N and P co-limitation (9-10) between years according to effects of seasonal rainfall patterns on N availability. Much of the discrepancy may be attributed to a greater dependence of annual grasses on the highly variable pools of available nutrients in soil compared with the buffered supply (via retranslocation from plant stores) available to perennials.…”
Section: Plant N:p Ratioscontrasting
confidence: 74%
See 2 more Smart Citations
“…1). This is also true for perennial grasses elsewhere in Australia (Norman, 1963;Christie, 1979;Friedel, 1981) but contrary to Turner's (1998a, b) finding that N : P ratios in annual grasslands changed from assumed P-limitation (14-17) to N and P co-limitation (9-10) between years according to effects of seasonal rainfall patterns on N availability. Much of the discrepancy may be attributed to a greater dependence of annual grasses on the highly variable pools of available nutrients in soil compared with the buffered supply (via retranslocation from plant stores) available to perennials.…”
Section: Plant N:p Ratioscontrasting
confidence: 74%
“…Moreover, many studies reported N : P ratios on a whole-plant or community basis rather than a plant component basis (Table 2). While this is consistent with the method of Koerselman and Meuleman (1996), data from the present and other studies of semi-arid grasslands (Norman, 1963;Christie, 1979;Friedel, 1981) demonstrate that N:P ratios vary between aboveground components in the order: litter'standing dead'green foliage'culms (e.g. Fig.…”
Section: Plant N:p Ratiossupporting
confidence: 52%
See 1 more Smart Citation
“…Using nylon-mesh litter bags anchored to the soil surface, Christie (1979) followed the decomposition of current season's litter produced by mitchell grass (Astrebla spp. ), a C 4 species widespread throughout the grasslands of western Queensland.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that grazing affects SOC levels, either through changes in plant community (Coupland et al, 1960;Dormaar and Willms, 1990;Coupland, 1992) or by other more subtle and less discernable responses such as litter accumulation and decomposition rates, changes in chemical composition of soil organic matter (SOM), amount and quality of root exudates, increased root biomass, and more rapid cycling of C (Schuster, 1964;Smoliak et al, 1972;Dyer and Bokhari, 1976;Davidson, 1978;Christie, 1979;Detling et al, 1979;Holland and Detling, 1990;Naeth et al, 1991;Shariff et al, 1994;Ganjegunte et al, 2005). The quantity and chemical composition of SOM is important to C and N cycling, as N is often the limiting factor to productivity in rangeland ecosystems (Power, 1994).…”
Section: Ja Morganmentioning
confidence: 99%